Higher Chlamydia trachomatis Prevalence in Ethnic Minorities Does Not Always Reflect Higher Sexual Risk Behaviour - Matser, Amy (Public Library of Science, 2013)
BACKGROUND: In affluent countries, the prevalence of Chlamydia trachomatis (CT) is often higher in certain ethnic minorities than in the majority population. In the Netherlands, we examined why CT prevalence is higher in Surinamese/Antilleans, the largest minority in the country. METHODS: Heterosexuals were recruited for a cross-sectional survey from May through August 2010 at the sexually transmitted infections (STI) clinic in Amsterdam. Participants completed a questionnaire and were tested for STI. A causal directed acyclic graph was assumed to investigate whether the association between ethnicity and CT could be explained by differences in sexual risk behaviour and socio-economic status. RESULTS: Subjects included 1044 with Dutch background and 335 with Surinamese/Antillean background. Median age for the combined population was 25 (IQR 22-30) years, and 55.4% was female. Sexual risk behaviour did not differ significantly between the two groups. CT was diagnosed in 17.9% of Surinamese/Antilleans and in 11.4% of Dutch. Surinamese/Antilleans were significantly more likely to have CT (OR 1.70; 95% CI 1.21-2.38). The association between ethnicity and CT remained statistically significant after adjusting for sexual risk behaviour, age, sex, and ethnic mixing (aOR 1.48; 95% CI 1.00-2.18), but not after adjusting for education and neighbourhood, markers of socio-economic status (aOR 1.08; 95% CI 0.71-1.64). CONCLUSION: The difference in CT prevalence between the minority and majority groups was not explained by differences in sexual risk behaviour. The higher CT prevalence found among Surinamese/Antilleans appeared to reflect their lower educational level and neighbourhood, two markers of lower socio-economic status. We hypothesise that the effect results from lower health-seeking behaviour.